KOMPARASI PEMAHAMAN KONSEP DAN GENERALISASI MATEMATIKA ANTARA STUDENT RESEARCH DAN DIRECT INSTRUCTION BERBANTUAN CABRI 3D - Wuryanto, Wuryanto; Kusni, Kusni; Sutarto, Hery (Jurnal Penelitian Pendidikan, 2012)
Geometry of space becomes a more difficult course compared with the basic geometry. Considerable evidence indicates the level of difficulty. In the geometry of space, students still have to transform three-dimensional objects into two-dimensional image field. This is related to spatial ability students. By combining the usefulness of mathematics and the development of science and technology it developed a mathematical model of teaching based on computer technology. The use of Cabri 3D in teaching space geometry was meant for the students to make educated guesses / conjectures, test conjectures, construct and make generalizations generally. The hope with the help of computers, the constraints and difficulties that exist can be eliminated little by little. The problems are going to be resolved through this study were 1). Are there differences in the ability of understanding the concept of school geometry student research through teaching strategies and direct instruction assisted Cabri 3D? 2). Are there differences in the ability of generalization through teaching strategies and direct student research Cabri 3D-aided instruction? The subject of this study is the fourth semester students of the school year 2010/2011 State University majoring in mathematics negei Semarang. The results showed 1). There were no differences in the ability of understanding the concept of school geometry student research through teaching strategies and direct instruction assisted Cabri 3D. 2). There are differences in the ability of generalization through teaching strategies student-assisted research and direct instruction Cabri 3D.